Analisis permasalahan dalam keterampilan menyimak pada kelompok belajar kelas IV di sekolah dasar - Afifah, Laela Nur Husnun; Rukayah, Rukayah; Daryanto, Joko (Didaktika Dwija Indria, 2021)
The aim of this research is to describe the abilities and problems in listening skills on the study group of 4th grade students of elementary school Bumi 1 No. 67 Surakarta in the academic year 2020/2021. This research regarding to four important elements, including listeners, speakers, talks, and situations and conditions. The method used in this research is descriptive qualitative with a phenomenological approach. The subjects used in this study were class teachers and 5 students who were members of one study group. The results of this research indicate that the ability of listening skills in the the 4th grade students of elementary school Bumi 1 No. 67 Surakarta in the academic year 2020/2021 is classified as low. The percentage of the total student results, namely 40% which states that 2 out of 5 students can reach the scores minimun (KKM). While 60% of the total percentage of students stated that 3 out of 5 students had a score below the set scores minimum (KKM). As for the problems in listening skills in the fourth grade study group can be found from every important element studied. The result of this research also encourage teachers to minimize the problems of listening skills